2022
DOI: 10.1002/jeab.784
|View full text |Cite
|
Sign up to set email alerts
|

Constructional fear treatment: Teaching fearful shelter dogs to approach and interact with a novel person

Abstract: Of the millions of dogs that enter animal shelters in the United States each year, many exhibit behaviors labeled as fear, which can decrease their likelihood of adoption. Current dog training procedures to treat these behaviors can take months or even years to show significant change. When these procedures are used in shelters, they mainly focus on reducing fear, as opposed to teaching specific behaviors to increase adoptions. The goal of the current study was to teach fearful shelter dogs to interact with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…(Goldiamond, 2022, p. 33, emphasis in original) CET directly addresses the operant cause, while respecting the classically conditioned origin of many of the phobic or highly reactive patterns. These procedures, which make the distance from the feared event contingent on alternative behavior without the use of extinction, are having a widespread effect in treating fearful and highly reactive animals (see Katz & Rosales-Ruiz, 2022 for an example of shaping with negative reinforcement for fearful animals). Early data suggest that CET procedures may produce less distress as a result of the emphasis on its constructional orientation, shaping of alternative patterns, and absence of extinction (Abdel-Jalil et al, 2023;Layng & Abdel-Jalil, 2022;Miller, 2022;Scallan & Rosales-Ruiz, 2023), as opposed to an emphasis being placed on "deepened extinction" (Craske et al, 2022) or escape extinction (Cuvo et al, 2010;Slifer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Goldiamond, 2022, p. 33, emphasis in original) CET directly addresses the operant cause, while respecting the classically conditioned origin of many of the phobic or highly reactive patterns. These procedures, which make the distance from the feared event contingent on alternative behavior without the use of extinction, are having a widespread effect in treating fearful and highly reactive animals (see Katz & Rosales-Ruiz, 2022 for an example of shaping with negative reinforcement for fearful animals). Early data suggest that CET procedures may produce less distress as a result of the emphasis on its constructional orientation, shaping of alternative patterns, and absence of extinction (Abdel-Jalil et al, 2023;Layng & Abdel-Jalil, 2022;Miller, 2022;Scallan & Rosales-Ruiz, 2023), as opposed to an emphasis being placed on "deepened extinction" (Craske et al, 2022) or escape extinction (Cuvo et al, 2010;Slifer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented positive correlations between time spent tail wagging and heart rate [17,23], although links between wagging and heart rate variability are less clear [12,23]. Tail wagging is frequently associated with both positive and negative arousal, suggesting a correlation with arousal-related hormones and neurotransmitters [24][25][26][27][28][29][30][31][32]. For example, there is indirect evidence linking oxytocin and tail wagging, especially when dogs are reunited with a familiar human [33,34].…”
Section: Tail Wagging and Tinbergen's Four Questionsmentioning
confidence: 99%
“…When designed from a multidisciplinary perspective including cognition, ethology, welfare, and behavior analysis, interventions can modify interactions between animals and their conspecifics or humans [18][19][20][21], resolve unwanted behaviors [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], temporarily increase enrichment usage, and expand the learner's behavioral repertoire [38] while ensuring good welfare. When an intervention's scope does not consider how the intervention impacts the learner, interventions focus on the elimination of behavior via punishment and aversive control [39], leading to outcomes that include fear, anxiety, pain, stress, aggression, and a negatively impacted dog-handler relationship [18,32,34,[40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses and their function based interventions successfully treated jumping up behavior [23,31], stereotypic behavior [29], resource guarding [27], kennel aggression and leash pulling in a shelter environment [37], demonstrated that access to the owner functions as a reinforcer for pet dogs [54], and showed that owners are capable of implementing FA and treatment of mouthing behavior [35]. Others demonstrated the success of interventions grounded in behavior analysis, using baseline measures to demonstrate treatment effectiveness [22,24,26,28,32,55]. As the body of literature pertaining to dog welfare and behavior interventions increases, so does the commitment to honoring the human-animal bond.…”
Section: Introductionmentioning
confidence: 99%